All Power To All the People: WGS and Feminist Pedagogy in the Era of the Alt-Right - Adair, Zakiya (Radical Teacher, 2021)
Academic Feminists have long used anti-oppression composition writing as a emancipatory pedagogical tool, but the impact of neoliberalism on higher education and the institutionalization of WGS have impacted how faculty teach these courses. As well the successful implementation of a gender course requirement has changed the demographics of these classes. This essay looks at the pedagogical parallels between teaching the gender studies course and the English composition course. An additional focus is how institutional shifts in WGS and its curriculum impact pre-tenure faculty's ability to offer emancipatory writing and teaching.